The Possibilities of Using Video in the Educational Process from the Point of View of Teachers and Adolescents - O.B. Konstantinova (Психолого-педагогические исследования)
The work is aimed at studying the possibilities of using videos in the educational process. The materials of two empirical studies obtained on a sample of teachers and students in grades 5-11 are presented. Study 1 (N=178) included respondents aged 10 to 18, of whom 54,5% were female; in study 2 (N=35) – aged 21 to 70 years, of which 88,6% were female. Both studies were carried out using the author's questionnaire "Possibilities of video at school" in two modifications – for teachers and schoolchildren in grades 5-11. The results of the answers of teachers and schoolchildren to questions about the frequency and ways of using video in a modern school and after 5 years are compared. The results show a significant excess of the activity of schoolchildren in the use of video in comparison with teachers and reflect the tendency for high school students to use the communicative and reflective capabilities of video. The prospects for using the reflexive analysis of video clips in the process of jointly distributed activities of adolescents to update the zone of proximal development are shown. It is concluded that it is possible to study the influence of the inclusion of video fragments of interaction on the development of communicative and reflexive abilities of adolescents in the process of joint solution of experimental research problems.